2016
DOI: 10.1016/j.jped.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The formation of citizens: the pediatrician's role

Abstract: In the light of the disclosed scientific evidence, the pediatrician emerges as the most differentiated professional to provide preventive and curative care indispensable to the skilled formation of a healthy citizen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Healthcare 2024, 12, 144 2 of 14 Pediatric residents consistently immerse themselves in a high-stress work environment-3-5 years of training full of uncertainties and diversities [9]. Evidence has shown that pediatric care is associated with stress from disease changes and fatigue in dealing with family members' anxieties [10]. Furthermore, studies have reported that residents who are depressed are more likely to make medical errors than their non-depressed peers [9].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare 2024, 12, 144 2 of 14 Pediatric residents consistently immerse themselves in a high-stress work environment-3-5 years of training full of uncertainties and diversities [9]. Evidence has shown that pediatric care is associated with stress from disease changes and fatigue in dealing with family members' anxieties [10]. Furthermore, studies have reported that residents who are depressed are more likely to make medical errors than their non-depressed peers [9].…”
Section: Introductionmentioning
confidence: 99%
“…O Transtorno do déficit de atenção e hiperatividade (TDAH) é uma condição neuropsiquiátrica que compromete o desenvolvimento do indivíduo, caracterizada por padrão persistente de desatenção e/ou hiperatividade e/ou impulsividade, afetando suas atividades sociais e de aprendizado (Campos et al, 2014).…”
Section: Introductionunclassified
“…The National Immunization Program (PNI), created in 1973, aims to standardize immunization at a national level with the aim of contributing to the control or eradication of infectious and vaccine-predictable diseases, including being an international reference for public health policy. It is reinforced that vaccination goes far beyond individual prevention (CAMPOS JÚNIOR; BURNS; LOPEZ, 2014).…”
Section: Introductionmentioning
confidence: 99%